2015
DOI: 10.1159/000374045
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Attenuated Low Ambient Temperature-Induced Myocardial Hypertrophy via Inhibiting Cardiomyocyte Apoptosis

Abstract: Background/Aims: Low ambient temperature is an important risk factor for cardiovascular diseases, and has been shown to lead to cardiac hypertrophy. In this study, we aim to investigate if Resveratrol may inhibit cold exposure-induced cardiac hypertrophy in mice, and if so to clarify its molecular mechanism. Methods: Adult male mice were randomly assigned to Control group (kept at room temperature), Cold group (kept at low air temperature range from 3°C to 5°C) and Resveratrol treatment group (100mg/kg/day) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…A growing body of evidence suggests that miRNAs play important roles in various cardiovascular diseases, particularly during disease development and progression, and treatments of cardiovascular disease based on miRNAs have important clinical significance [27]. Therefore, the identification of miRNAs that are closely associated with cardiovascular disease is important.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that miRNAs play important roles in various cardiovascular diseases, particularly during disease development and progression, and treatments of cardiovascular disease based on miRNAs have important clinical significance [27]. Therefore, the identification of miRNAs that are closely associated with cardiovascular disease is important.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 is a pivotal molecule in many apoptosis pathways and it exerts inhibitory effect on free radical elevation, calcium overload and lipid peroxidation, and thus the protective role of Res is probably to be achieved by changing the expression of Bcl-2 and Bax. A recent study reported that RES administration could inhibit cold exposure-induced cardiac hypertrophy in mice and had a suppressive action of apoptosis of myocardium via inhibition of Bax and caspase-3 activation [29].…”
Section: Discussionmentioning
confidence: 99%
“…How to prevent cold-induced myocardial hypertrophy is essential for the therapeutics of cold-related diseases. Our previous study reported that Resveratrol inhibited cold-induced heart hypertrophy via suppressing miR-328 expression and apoptosis [7]. In this study, we detected the effects of Atv on blood pressure, cardiac function, cardiomyocyte hypertrophy, cardiac fibrosis and potential signaling pathways in cold-treated mice.…”
Section: Discussionmentioning
confidence: 82%
“…The Kunming adult male mice used in this study were purchased, raised and grouped as previous study [7]. 10mg/kg Atv was given to mice by gastric gavage in Atv group, and Ctl as well as Cold groups were treated with isovolumic PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation